Potret Masyarakat Urban dalam Cerpen Vampir dan Darah Karya Intan Paramadhita - Ilham Maulana; Imam Muhtarom; Dewi Herlina Sugiarti (Peneliti.net, 2022)
This study aims to examine urban portraits in the collection of short stories Sihir Perempuan by Intan Paramaditha. The approach used in this research is a qualitative approach with a descriptive method. The results showed that in the short story Vampire, the physical aspects of urban society were found, namely (1) social heterogeneity in the difference in social status between Irwan and Saras, (2) The secondary relationship in the short story is characterized by the lack of personal interaction involving the two, (3) high mobility The city lies in Saras' desire to develop his potential as a secretary where increasing work competence will also increase social status in society, (4) Individualization as a result of a person's high level of education so that he feels able to determine what is best for him without pressure from others narrated by Intan Paramaditha through Saras who accepted Irwan's offer without asking other people's considerations, and (5) Spatial segregation was raised through the discussion of cafes and stalls that marked the urban aspect